Pemanfaatan AI dalam Mendukung Aktivitas Pembelajaran Mahasiswa PAI Berbasis Literasi Digital - Via Hanadya Safitri, Marcelina; Susilo, Muhammad Joko (Education Reserach Center, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact on the world of education today, particularly for Islamic Education (PAI) students in their learning processes. This study aims to explore how the utilisation of AI can support the learning activities of PAI students based on digital literacy. The research adopts a qualitative approach with a library research design. The data analysis technique used is content analysis. The findings show that AI holds great potential, as it can personalise learning, provide interactive and engaging learning media, and contribute to the development of 21st-century skills such as critical thinking, problem-solving, and creativity. The integration of AI into each PAI course presents opportunities to enhance the effectiveness and efficiency of learning, tailored to the individual needs of students. Nevertheless, challenges such as limited infrastructure in remote areas, low levels of digital literacy, ethical concerns, and dependence on AI technology remain obstacles that need to be addressed. Therefore, it is necessary to strengthen students’ digital literacy and ethical use of technology, grounded in Islamic principles, so that AI can function as an effective tool to support learning in each course. This serves as a strategy to maximise the use of AI technology in the PAI education process